2018
DOI: 10.5194/acp-2018-49
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light absorption of brown carbon in eastern China based on 3-year multi-wavelength aerosol optical property observations at the SORPES station and an improved Absorption Ångstrom exponent segregation method

Abstract: Abstract. Brown carbon (BrC), a certain group of organic carbon (OC) with strong absorption from the visible to ultraviolet (UV) wavelengths, makes considerable contribution to light absorption on both global and regional scales. High concentration and proportion of OC has been reported in China, but studies of BrC absorption based on long-term observations are rather limited in this region. In this 20 study, we reported 3-year results of light absorption of BrC based on continuous measurement at the Station f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…found that the use of aromatic chromophores with visible light trapping ability and appropriate excited-state energy levels could effectively enhance the visible light absorption ability of certain transition metal complexes and prolong the triplet-state lifetime . In this way, the low-energy excited states (either singlet or triplet states) can be switched from the conventional metal-to-ligand charge transfer to π–π* states, while the ISC process of π–π*→ π–π* is often efficient, and the spin–orbit coupling (SOC) of the π–π* state leads to a longer-lived T 1 state due to the larger energy gap of the T 1 / S 0 state. ,, Although previous studies have focused on rare metals such as Ru, its homologue Fe retains a similarity to rare metals in studies on the properties of metal-to-ligand charge transfer excited states, which should be an important reason for the increased yield of the triplet state in the Fe 3+ -coupled system for highly oxidative HULIS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…found that the use of aromatic chromophores with visible light trapping ability and appropriate excited-state energy levels could effectively enhance the visible light absorption ability of certain transition metal complexes and prolong the triplet-state lifetime . In this way, the low-energy excited states (either singlet or triplet states) can be switched from the conventional metal-to-ligand charge transfer to π–π* states, while the ISC process of π–π*→ π–π* is often efficient, and the spin–orbit coupling (SOC) of the π–π* state leads to a longer-lived T 1 state due to the larger energy gap of the T 1 / S 0 state. ,, Although previous studies have focused on rare metals such as Ru, its homologue Fe retains a similarity to rare metals in studies on the properties of metal-to-ligand charge transfer excited states, which should be an important reason for the increased yield of the triplet state in the Fe 3+ -coupled system for highly oxidative HULIS.…”
Section: Resultsmentioning
confidence: 99%
“…Brown carbon (BrC) aerosols, which can absorb near-ultraviolet and visible light, are important contributors to the radiative forcing and the greenhouse effect in the troposphere . As an important component of BrC, humic-like substances (HULIS) can also produce active intermediates, such as triplet organics and reactive oxygen species (ROS) via photochemistry, ,, and further initiate the aging process of organic aerosols in the particle phase. For example, it has been found that triplet organics can oxidize isoprene and induce a portion of ROS, such as hydroxyl radical ( · OH), single oxygen ( 1 O 2 ), and superoxide (O 2 ·– ). , The atmospheric concentrations of HULIS, which mainly originated from terrestrial biomass burning (11–36%) and coal combustion (11–41%), are in the range of 0.39–13.4 μg·m –3 in China. …”
Section: Introductionmentioning
confidence: 99%
“…The light absorption coefficient of WSOC at 365nm is used to represent water-soluble BrC, which is organic carbon with a capacity of absorbing radiation (Yan et al, 2015;Hecobian et al, 2010;Wang et al, 2018a). The mean babs value was 9.4 ± 4.8 M m -1 , higher than the summertime value but lower than the wintertime value in Beijing and Guangzhou (Yan et al, 2015;Qin et al, 2018).…”
Section: Light-absorbing Propertymentioning
confidence: 99%
“…In addition, recent studies also suggest that BrC emitted from biomass burning is unstable due to chemical losses (Forrister et al., 2015; X. Wang, Heald, et al., 2016). The decay of BrC absorption due to photobleaching associated with aging processes could result in a 50% decrease of its DRF (Brown et al., 2018; X. Wang, Heald, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…S. Li et al (2018), Liakakou et al (2020), Meng et al (2020), Mo et al (2021), Park et al (2020, 2018), Park and Yu (2016), Peng et al (2020), Y. Qin et al (2018), Satish et al (2020, 2017), Shen et al (2017), Soleimanian et al (2020), J. Sun et al (2021, 2016, 2017), Tang et al (2020), Tian et al (2019), Voliotis et al (2017), J Wang, Nie, et al (2018),. Y., M Xie et al (2019Xie et al ( , 2017Xie et al ( , 2018,.…”
mentioning
confidence: 99%